The Yatela gold deposit in Mali, West Africa: The final product of a long-lived history of hydrothermal alteration and weathering. (January 2016) - Masurel, Quentin; Miller, John; Hein, Kim A.A.; Hanssen, Eric; Thébaud, Nicolas; Ulrich, Stanislav; Kaisin, Jean; Tessougue, Samuel
Abstract: The Yatela gold deposit is located in the Kédougou-Kénieba inlier (KKI), a window of ca. 2200-2050 Ma rocks that are exposed in eastern Senegal and western Mali. The geology of the KKI differs from other Paleoproterozoic granite-greenstone belts and sedimentary basins by the abundance of carbonate rocks. The Yatela deposit occurs within 8 km of the regional-scale Senegal–Mali Shear Zone. Country rocks in the Yatela region have been subjected to polycyclic deformation and regional greenschist-facies metamorphism. A syn-kinematic diorite stock has intruded the metasedimentary sequences in the open pit and is associated with a hornblende-hornfels contact aureole. Field relationships and micro-textural data indicate that the primary gold mineralisation is shear-hosted. The similar relative timing and structural setting between the Yatela primary gold mineralisation and other world-class deposits in the region (e.g., Loulo, Lawrence et al., 2013a; Massawa, Treloar et al., 2014; Sadiola Hill, Masurel et al., in press) suggest that regional orogenic gold mineralisation occurred during a period of transcurrent tectonics, after the cessation of regional compressional deformation. The primary gold mineralisation at Yatela, however, is low-grade and sub-economic. It is hosted by marbles and, to a lesser extent, diorite. The primary ore is pyrite-rich, with abundant chalcopyrite, minor arsenopyrite and accessory Zn–Pb–Sb–Fe–Ag–Co–Ni-bearing mineral species. Post-Birimian surficial dissolution of hydrothermally altered and mineralised host marbles resulted in the creation of troughs, which were draped and infilled with a ferruginous dissolution residue enriched in gold. This auriferous residuum formed the economic resource mined at Yatela until decommissioning in 2013. The Yatela gold deposit is unique with respect to mineralisation types encountered in West Africa because an auriferous residuum of economic interest (>1 Moz) derives from an underlying sub-economic Birimian occurrence. This study provides a new appreciation for the economic interest of Yatela-style orebodies and their prospectivity in other gold provinces of the West African Craton where carbonates are present, such as in the Siguiri basin in Guinea and the Ity region in western Côte d'Ivoire. Highlights: The primary carbonate-hosted gold mineralisation is orogenic in style. Post-Birimian weathering processes resulted in residual and supergene gold enrichment. An auriferous residuum of economic interest (>1 Moz) derives from an underlying sub-economic Birimian occurrence.